Analisis Teknikal Menggunakan Moving Average (MA), Moving Average Convergence-Divergence (MACD), dan Relative Strength Index (RSI) Untuk Mengoptimalkan Dalam Pengambilan Keputusan Investasi Pada Saham Sektor Manufaktur Index LQ45 BEI Tahun 2022-2023 - Saiful Hasan; Siti Nurhasanah; Wahyu Purbo Santoso (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research examines technical stock analysis techniques for six manufacturing sector companies listed on the Indonesia Stock Exchange for the 2022–2023 period, using the Moving Average (MA), Moving Average Convergence and Divergence (MACD) and Relative Strength Index (RSI) indicators. . Astra International Tbk (ASII), PT Indofood Sukses Makmur Tbk (INDF), PT Indofood CBP Sukses Makmur Tbk (ICBP), PT Semen Indonesia Persero Tbk (SMGR), PT Indah Kiat Pulp & Paper Tbk (INKP), and PT Kalbe Farma Tbk (KLBF) are some of them. The analysis was conducted using charts from the stockbit.com website to evaluate the accuracy of signals and the investment performance of these three indicators. The research results indicate that RSI has the highest signal accuracy rate, namely 92%, while MA and MACD have accuracy rates of approximately 58% and 55%, respectively. Despite MACD producing more signals, RSI remains accurate with fewer signals. In terms of return on investment, RSI achieved a total return of 238%, followed by MACD with a total return of 161%, and MA with a total return of 101%. RSI proves to be a reliable indicator by generating positive returns without any negative returns on the studied stocks. In conclusion, RSI is the primary choice in making investment decisions in the manufacturing sector stocks on the Indonesia Stock Exchange due to its accuracy and positive investment returns. However, MA remains useful for trend analysis, and investors are advised to pay attention to the entire stock market, consider additional indicators, and have sufficient understanding of technical analysis. For future research, it is recommended to consider other sectors and a broader range of indicators.